Identification of the paraproteins and clinical significance of more than one paraprotein and clinical significance of more than one paraprotein in serum of 56 patients. Issue 4 (April 1979) - Gore, M E; Riches, P G; Kohn, J
Abstract : Sera from 56 patients with more than one paraprotein were investigated for immunoglobin class and light chain type of each paraprotein. The patients were divided into two groups according to the diagnosis, that is myeloma and macroglobulinaemia or others. The frequency of combinations of paraproteins was considered in the whole series and in the two groups. The laboratory and clinical findings were analysed to investigate the diagnostic and prognostic significance of more than one paraprotein in a serum. It is concluded that a lower percentage of patients with more than one paraprotein can definitely be shown to have myeloma than might be expected from studies on monoclonal paraproteinaemia, that patients having IgA paraproteins in the serum had the poorest prognosis, and that paraproteins with lambda light chains were more likely to be associated with myeloma or macroglobulinaemia. A discriminant analysis of ESR and total paraprotein levels in the two groups of patients showed that combinations of the two parameters were not more effective at distinguishing the groups than the ESR alone.